EU COMPETITION LAW IN THE DIGITAL ERA: WHAT TO TELL ABOUT INTEL? (EU and comparative law issues and challenges series (ECLIC), 2018)
Intel, a US-based company, was fined by the European Commission in 2009 for abusing its dominant position at the computer processor market intended to exclude its competitor AMD from that market. The penalty amounting to €1.06bn was the largest antitrust fine in the Commission’s history at the time. As the EU General Court had rejected Intel’s appeal in 2014, the matter was brought before to EU Court of Justice. The CJEU judgment, rendered in September 2017, is controversial for at least two reasons. First is the territorial reach of the EU competition law outside the EU borders, and second relates to the treatment of exclusivity rebates. With regards to the former, for the first time the CJEU confirmed the position of the Commission and the General Court regarding the extended territorial reach of the EU antitrust legislation. Quite the opposite, the CJEU quashed the General Court ruling as to the former, arguably rejecting the traditional per se infringement of exclusivity rebates and embracing the effects-based analysis. The doctrine is somewhat divided as to whether this judgment is a much needed clarification of the two issues or it indicates a new direction in EU competition law analysis. This paper is addressing the most important ideas in the doctrinal interpretations and related arguments, and provides critical assessment of the present state of affairs. It also raises certain points relevant to the Intel judgment, which so far have not been given sufficient attention in the case comments and scholarship.